2022
DOI: 10.3390/f13101538
|View full text |Cite
|
Sign up to set email alerts
|

Analytical Model for the Load-Bearing Capacity Analysis of Winter Forest Roads: Experiment and Estimation

Abstract: In northern forests, winter is the preferred time for logging operations, since, when wet soils freeze, their strength increases, which ensures a high load-bearing capacity of winter forest roads and reduces the cost of forestry work by increasing the load on forestry equipment, including when driving through frozen lowlands. The present article analyzes frozen loamy–sandy soil, which, at subzero temperatures, behaves like a brittle material with a sufficiently high, but limited, strength. Well-known models co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 35 publications
0
7
0
Order By: Relevance
“…Considering only the external aspects of the behavior of the material under load, we used the concept of structural stiffness (the stiffness of materials is usually characterized by the modulus of elasticity). Analysis of the behavior of heterogeneous materials, such as frozen ground, rocks, and concrete, also confirmed the effectiveness of this approach [36,45]. The main issue of this work was to determine the criterion for transition from the quasi-elastic behavior of wood to the quasi-plastic stage.…”
Section: Discussionmentioning
confidence: 63%
See 2 more Smart Citations
“…Considering only the external aspects of the behavior of the material under load, we used the concept of structural stiffness (the stiffness of materials is usually characterized by the modulus of elasticity). Analysis of the behavior of heterogeneous materials, such as frozen ground, rocks, and concrete, also confirmed the effectiveness of this approach [36,45]. The main issue of this work was to determine the criterion for transition from the quasi-elastic behavior of wood to the quasi-plastic stage.…”
Section: Discussionmentioning
confidence: 63%
“…This paper uses the Blagojevich analytical model [34], which belongs to the class of simple but sufficiently versatile load-displacement models, a review of which can be found in [35]. The application of modifications of this model to the analysis of frozen soils and some rocks is considered in [36,37]. However, when applying this model to the analysis of wood, it is necessary to take into account features that have not been previously considered in sufficient detail in the known literature.…”
Section: Load-displacement Curve In Compression Tests Of Wood Along T...mentioning
confidence: 99%
See 1 more Smart Citation
“…The study [5] shows that labor productivity has a strong impact on the economic growth rate of the construction industry in the regions of Northwestern Russia, including the Republic of Karelia. Speaking about the labor productivity growth and production efficiency, it is noted that the regional logistics system development plays one of the key roles in achieving positive indicators dynamics [6][7][8][9][10][11][12][13][14][15][16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…The study [18] accesses the logistics systems formation construction from the perspective of digitalization. Researches [4,6,7,8,10,12,16] are devoted to transport planning, the use of economic and mathematical methods in the transport systems construction and the application of logistics principles of development in the region.…”
Section: Introductionmentioning
confidence: 99%